Pengembangan UMKM Olahan Pangan di Provinsi Gorontalo Menggunakan Pendekatan Sistem Dinamik - Faradiba Faruk Zubedi; Lukman Mohammad Baga; Netti Tinaprilla (Jurnal Ilmu Pertanian Indonesia, 2024)
Processed food SMEs in Gorontalo Province are one of the sectors contributing to regional economic development. The government implements policies and programs to develop competitive processed food SMEs. This study aims to analyze the formulation of policies for the development of processed food SMEs, with the hope of optimizing the production and added value of these SMEs through increasing production volume and market access. This study used a quantitative approach using primary data and secondary data in the form of time series. A dynamical system method with six scenarios is used and simulated until 2045. The results showed that the best scenario for achieving the research objectives was scenario six. Scenario six is carried out by simulating business capital assistance programs as well as increasing partnerships, business legality, and digitalization simultaneously. The production volume of processed food SMEs will reach 764,352 pcs in 2045, with a market access value of 41.67%. Policies need to focus on business financing and increasing the business capacity of processed food SMEs in Gorontalo province. The results of the policy simulation can be considered in realizing the achievement of accelerating the development of competitive SMEs, as stated in the Long-Term Development Plan of Gorontalo Province. Keywords: dynamic policy, Gorontalo Province, processed food, SMEs Processed food SMEs in Gorontalo Province are one of the sectors contributing to regional economic development. The government implements policies and programs to develop competitive processed food SMEs. This study aims to analyze the formulation of policies for the development of processed food SMEs, with the hope of optimizing the production and added value of these SMEs through increasing production volume and market access. This study used a quantitative approach using primary data and secondary data in the form of time series. A dynamical system method with six scenarios is used and simulated until 2045. The results showed that the best scenario for achieving the research objectives was scenario six. Scenario six is carried out by simulating business capital assistance programs as well as increasing partnerships, business legality, and digitalization simultaneously. The production volume of processed food SMEs will reach 764,352 pcs in 2045, with a market access value of 41.67%. Policies need to focus on business financing and increasing the business capacity of processed food SMEs in Gorontalo province. The results of the policy simulation can be considered in realizing the achievement of accelerating the development of competitive SMEs, as stated in the Long-Term Development Plan of Gorontalo Province. Keywords: dynamic policy, Gorontalo Province, processed food, SMEs